AB0018 Clinical status and gene expression in class iv lupus nephritis. (12th June 2018) - Mas, L.A.; Saurit, V.; Palomino, E.; De la Fuente, J.L.; Angelina, M.; Alejandro, A.; Alvarellos, T.
Abstract : Background: Lupus nephritis (LN) is one of the most frequent and serious complications in the patients with systemic lupus erythematosus. Several studies have identified risk factors for poor kidney prognosis in patients with SLE, including age, sex, hypertension, decreased estimated GFR (eGFR), proteinuria, and renal pathologic types. 1 Biopsy allows classifying the type of renal involvement, assessing its activity, and thus guiding the therapeutic behaviours. It has been shown that structural changes and inflammatory infiltrate associated with LN contribute to a hypoxic state which induces angiogenesis. 2 Herein, it was hypothesised that differential expression of angiogenic genes could classify Lupus Nephritis Patients (LNP) with the same histological score but different "clinical status". Objectives: To investigate if there is a differential angiogenic gene expression in biopsies of LNP under the same histological classification but different "clinical status" measured by eGFR. Methods: Twenty four kidney biopsies samples classified according to ISN/RPS scoring system as Class IV from 24 LNP were divided into eGFR <60 ml/min (n=10, age: 31.00±10.93, range: 17–46) and eGFR >60 ml/min (n=14, age: 32.64±11.34, range: 21–64). RNA was isolated using TRIzol-Chloroform technique and then was reverse-transcribed using random primers. Gene expression level of pro-angiogenic factors: VCAM-1, VEGF, TGF-β and ANGPT-1 were evaluated using Quantitative Real Time PCR (QPCR). The threshold cycle (Ct) scores were averaged for calculations of relative expression values. The Ct scores were normalised by subtracting β2Microglobuline (β2M) control, or ΔCt=Ct, gene- Ct, β2M. To test for differential gene expression between groups, a two sample T-test was performed to compare the ΔCt in the two groups. Results: ΔCt is inversely proportional to the gene expression level. Significant differences between groups was found in VEGF-A gene (p=0.0326), where the greatest expression corresponding to eGFR <60 ml/min group. However, there were not statistically significant differences in VCAM-1, ANGPT1 and TGF-β expression (table 1). Particularly TGF-β, a proangiogenic and profibrotic gene showed a uniform expression level in both groups. Conclusions: In the present cross-sectional study, increased levels of VEGF-A were observed in biopsies Class IV from LNP with eGFR <60 ml/min. These findings suggest a differential gene expression that may be associated with an impaired renal function, reflected by eGFR. References: [1] Thong B, Olsen NJ. Systemic lupus erythematosus diagnosis and management. Rheumatology (Oxford)2017;56(suppl_1):i3–13. [2] Carmeliet P, Jain RK. Molecular mechanisms and clinical applications of angiogenesis. Nature2011;19:298–307. [3] Weening JJ, et al. The classification of glomerulonephritis in systemic lupus erythematosus revisited. Kidney Int2004;65(2):521–30. Disclosure of Interest: None declared